Infeasible Desires of Women in Girish Karnad’s Selected Plays - Prabhakar Madella; Brij Govind (Journal of Biomedical and Pharmaceutical Research, 2023)
This article is a humble attempt to search the identity of women in the patriarchal society prevailing in India. The condition of women in India has undergone several alterations since past millennia. During the Vedic time, women enjoyed a higher status and were extolled to the heights of Heaven by epitomising her as Goddess. Gradually with the passage of time women lost their status and dignity. She is regarded as an abla, a weak and helpless lady who depends upon man for her existence and sustenance. Indian Literature viewed women as role bound possession whose sacrifices preserved the sanctity and the well being of the family. Literature has always been ambivalent in its representation of women. Writers observed that women had become a heated argument and they started portraying them in their works. They drew inspirations from the real life incidents, which talked about liberating the images. This article traces the paradigm shift where women emerge despite all obstacles to hold her identity in personal and professional life. This paper aims at portraying, the women is no more an accessory to man rather she is a companion, a life partner who is equal to men in all aspects. Keywords- Women, obstacle, patriarchal, alteration, existence